2007
DOI: 10.1097/01.ogx.0000269073.50925.38
|View full text |Cite
|
Sign up to set email alerts
|

American Cancer Society Guidelines for Breast Screening With MRI as an Adjunct to Mammography

Abstract: New evidence on breast Magnetic Resonance Imaging (MRI) screening has become available since the American Cancer Society (ACS) last issued guidelines for the early detection of breast cancer in 2003. A guideline panel has reviewed this evidence and developed new recommendations for women at different defined levels of risk. Screening MRI is recommended for women with an approximately 20-25% or greater lifetime risk of breast cancer,including women with a strong family history of breast or ovarian cancer and wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
874
1
33

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 606 publications
(920 citation statements)
references
References 56 publications
11
874
1
33
Order By: Relevance
“…We classified respondents aged 50 years and older as being up to date with CRC screening if at least one of the following conditions were met: fecal occult blood test received within the past year, sigmoidoscopy within the past 5 years, or colonoscopy within the past 10 21 Because women with FMH profiles of early-onset breast or ovarian cancer may be encouraged to initiate breast cancer screening at an earlier age than average-risk women, 22 we examined the prevalence of women aged 30 years and older receiving a mammogram within the past year. We used SAS v9.2 (SAS Institute, Cary, NC) and SAS callable SUDAAN release 10 (Research Triangle Institute, Research Triangle Park, NC) to conduct all analyses to account for the complex sampling design of CHIS.…”
Section: Variables and Statistical Analysismentioning
confidence: 99%
“…We classified respondents aged 50 years and older as being up to date with CRC screening if at least one of the following conditions were met: fecal occult blood test received within the past year, sigmoidoscopy within the past 5 years, or colonoscopy within the past 10 21 Because women with FMH profiles of early-onset breast or ovarian cancer may be encouraged to initiate breast cancer screening at an earlier age than average-risk women, 22 we examined the prevalence of women aged 30 years and older receiving a mammogram within the past year. We used SAS v9.2 (SAS Institute, Cary, NC) and SAS callable SUDAAN release 10 (Research Triangle Institute, Research Triangle Park, NC) to conduct all analyses to account for the complex sampling design of CHIS.…”
Section: Variables and Statistical Analysismentioning
confidence: 99%
“…BREAST MAGNETIC RESONANCE imaging (MR) is gaining acceptance for screening in high-risk patients, detection of occult breast cancer, and the evaluation of response to neo-adjuvant treatment (1)(2)(3)(4). Breast MR is currently also being evaluated for preoperative staging (5).…”
mentioning
confidence: 99%
“…When using new KNN, the classification performance level of the interactive CAD system is significantly increased (p < 0.001) to AUC 00.897 with the corresponding 95% CI of [0.887, 0.907]. (1) to the bottom right ROI (12), the reference image set of CC view includes three ROIs (6, 9, and 10) depicting malignant masses, three ROIs (3, 5, and 11) depicting benign masses, and six ROIs (1, 2, 4, 7, 8, and 12) depicting CAD-cued falsepositive regions, while the reference image set of MLO view includes five malignant ROIs (3,5,6,9, and 12), one benign ROI (2), and six CAD-cued false-positive ROIs (1,4,7,8,10, and 11) Fig. 4 Comparison of two ROC-type performance curves of our interactive CAD scheme evaluated using a leave-one-out testing method involving 3,600 ROIs in the reference database.…”
Section: Resultsmentioning
confidence: 99%
“…Scientific research has found that earlier detection of breast cancer could reduce not only treatment cost but also patients' mortality and morbidity rates [2]. Although a number of screening tools such as breast magnetic resonance imaging [3,4] have been approved and used as adjunct screening tools for the highrisk women identified by epidemiology-based risk models [5], periodic screening with mammography is the only clinically accepted imaging modality for screening the general population to date. However, interpreting mammograms by radiologists is difficult and time-consuming due to the low cancer prevalence in the screening environment (i.e., less than three to five cancers detected per every 1,000 screening examinations), as well as a large variability of depicted breast abnormalities and overlapped dense fibro-glandular tissue on the two-dimensional projected images [6,7].…”
Section: Introductionmentioning
confidence: 99%